Development and validation of a machining fixture for complex-shaped components based on Plückerian matrix approach and SDT concept - Mustapha, Arslane (Université de M'sila, 2020)
In the manufacturing industry, there are several types of parts of complex shapes owning various functions. The turbine blades (buckets and vanes) are one of the most important components in gas turbines. However, these blades have complex shapes and irregular surface curvature which make them difficult to machine. Production of such kind of parts is so complicated and requires a high control of machining process, advanced CNC programming, innovative tools, and special fixtures allowing to maintain exactly and rigidly in a unique position of the part during machining. In order to enhance productivity and reduce operation time, thereby increasing parts quality, the machining fixture has to fulfill several requirements such as allowing a correct location with security and repeatability of the workpiece as well as maintaining conformity and interchangeability of the machined parts. This paper addresses the challenge of machining complex geometry parts by development and realization of a dedicated machining fixture (MF) for holding a mobile blade of a gas turbine. The first novelty of this work is in the application of the Plückerian coordinates method for choosing the locator’s placement of complex-shaped parts. The choice of the locator’s placement during the design process of the fixture is performed based on the maximization of the determinant and minimization of the condition number of the locator matrix (information matrix). The second novelty is in the optimization approach used. The last novelty is in the developed and fabricated machining fixture. The performance of the developed fixture in terms of localization repeatability is evaluated based on the small displacement torsor (SDT) concept. Results show the validity of the developed fixture.
Keywords: Machiningfixture . Plückerianmatrix .Locator’splacement .Small displacement torsor .Turbineblade .Repeatability